Mapping access to medical service provision at micro-scale: Dynamics in supply and demand in Germany - Reiter, Denis; Hecht, Robert; Jehling, Mathias (Raumforschung und Raumordnung | Spatial Research and Planning, 2024)
This paper demonstrates an approach to the problem of micro-scale analysis of medical service provision in Germany. Research focuses include estimating population dynamics, mapping access to medical facilities and identifying spatial patterns in medical service provision. We applied the Enhanced Two Step Floating Catchment Area method to quantify changes in access to primary care physicians over a period of eleven years. Our study reveals that overall access is modestly rising, but significant spatial disparities exist between different regions of Germany. We describe both supply and demand issues behind the observed changes in access. As a key result, we identify four types of regions with differing access-population dynamics. Our main conclusion on the topic of medical service provision is that spatial planning is facing a multi-dimensional problem rather than a one-dimensional one, and that access to services depends on a combination of factors. Concerning differences between rural and urban regions, we find that that there is no general positive or negative trend for either.